PENGEMBANGAN MEDIA PAPAN FLANEL UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK DI MI/SD - Asrin Nasution; Aninditya Sri Nugraheni (STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The urgency of educational media as assistive equipment in delivering educational modules is also on the flannel board media which aims to improve students' conceptual descriptions in mastering the water cycle module lessons. The results of the research and development that were tried shared an explanation that: the Flannel Board Media product that has been raised is